1998
DOI: 10.1111/j.1471-0528.1998.tb09969.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review comparing continuity of midwifery care with standard maternity services

Abstract: Objective To review randomised controlled trials of alternative maternity services characterised by continuity of midwifery care.Methods A systematic review of randomised controlled trials, analysed on an intention to treat basis, in which the study intervention was characterised by a midwife or small group of midwives providing care from early pregnancy to the postnatal period (defined as that provided on the postnatal ward); and the controls by standard maternity care as practised in the place where the tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 19 publications
(61 reference statements)
3
61
0
3
Order By: Relevance
“…The findings demonstrated a significant difference in the caesarean rate between the community group and the control group. COC has been shown to reduce interventions in labour, particularly augmentation of labour, analgesic use and electronic foetal monitoring [47].…”
Section: Patients' Perspective On Lack Of Trust and Involvement As Wmentioning
confidence: 99%
“…The findings demonstrated a significant difference in the caesarean rate between the community group and the control group. COC has been shown to reduce interventions in labour, particularly augmentation of labour, analgesic use and electronic foetal monitoring [47].…”
Section: Patients' Perspective On Lack Of Trust and Involvement As Wmentioning
confidence: 99%
“…The emergency caesarean reduction might be attributable to continuity of midwifery care during labour. Differences in caesarean section rates have not been demonstrated in most other trials of continuity of midwifery care, 21 although a trend to a reduction in high risk women has been reported. 7;9 A trial of 200 women in Canada did demonstrate a significant difference.…”
Section: Reduced Caesarean Section Ratementioning
confidence: 93%
“…17 Similar trials have shown a small, non-statistically significant increase in perinatal deaths associated with the continuity of care models 6;9;19;22;23 and a recent systematic review cited this increase as a major concern. 21 Our study is important as it adds to the relatively small numbers available for meta analysis to this point.…”
Section: Perinatal Mortalitymentioning
confidence: 99%
See 2 more Smart Citations